PENGARUH VIDEO EDUKASI TERHADAP TINGKAT PENGETAHUAN KESIAPSIAGAAN BENCANA GEMPA BUMI PADA SISWA SDN 1 PUNDONG BANTUL YOGYAKARTA: Pengaruh Video Edukasi Bencana Gempa Bumi Terhadap Tingkat Pengetahuan Kesiapsiagaan Bencana Gempa Bumi Pada Siswa SDN 1 Pundong Bantul, Yogyakarta - Antari, Rizkika Dwi; Setyaningrum, Niken (Ruang Ide Publisher, 2023)
Background : Disaster is a natural or non-natural process that causes casualties of life, property and disrupts the order of life, one of which is an earthquake. An earthquake is an earth-shaking event caused by collisions between earth plates, fault activity (faults), volcanic activity, or rock collapse. Earthquakes can destroy buildings, roads, bridges, and so on in an instant. Efforts to reduce the impact that can be caused by earthquakes are by increasing knowledge of disaster preparedness through educational videos given from an early age to elementary school students because children are vulnerable to disasters. Therefore it is very important to avoid or minimize the risk of becoming a victim. Objective : To determine the effect of educational videos on the level of knowledge of earthquake disaster preparedness in grade 4 and 5 students at SDN 1 Pundong Bantul, Yogyakarta. Method : This study used a pre-experimental research design with a one group pretest and posttest approach. The sample technique uses total sampling. The study population was students of SDN 1 Pundong Bantul, Yogyakarta. With a sample of 37 respondents. Data analysis using Wilcoxon Signed Rank Test. Results : There is an influence of educational videos on the level of knowledge of earthquake disaster preparedness in students of SDN 1 Pundong Bantul Yogyakarta with a value of p-value = 0.000 (<0.05). Conclusion : Students' knowledge about earthquake disasters can be improved by providing educational videos about earthquake disasters.